Praktik konseling dalam pola pengasuhan Islami - Niammil Fathni (Universitas Mathla'ul Anwar Banten, 2026)
The time of big changes in education needs early learning places to be creative and flexible as technology, society, and how we learn change quickly. This study looks at how important it is for teachers to have good emotional intelligence and the ability to adapt when teaching kids with special needs in early childhood settings. The research used a qualitative method with a case study to look at an inclusive early childhood school. Information was gathered through watching what happened, talking to people, and looking at records. The findings show that teachers who have strong emotional intelligence are better at understanding the unique needs of each child with special needs and can change their teaching methods to fit those needs. Also, a teacher's ability to use technology and change how lessons are presented is very important for getting inclusive education right in today's digital world. In short, the combination of emotional intelligence and adaptability in teachers is a key part of creating a good learning environment for all children.